Lupus Nephritis PathoProfile - Cheung, Annie; Deng, Arlinda; Zhu, Annie (The Meducator, 2013)
Lupus nephritis (LN) is the inflammation of the kidney caused by systemic lupus erythematosus (SLE), which is an autoimmune disease involving neutrophils. Neutrophils are a class of circulating immune cells that can immobilize and kill invading microbes by generating neutrophil extracellular traps (NETs). In usual circumstances, NETs are removed from the body in order to maintain tissue homeostasis and avoid autoimmunity. However, it has been implicated that there is an impairment of NET degradation in LN, resulting in the initiation of an auto-inflammatory response that involves the production of autoantibodies against neutrophil DNA and proteins. LN is characterized by renal inflammation, progressive renal dysfunction, and often mortality.